ANALISIS PENGELOLAAN KEUANGAN DESA LUBUK SAKAT DALAM MEWUJUDKAN PEMBANGUNAN DESA LUBUK SAKAT TAHUN 2012 - ", Febrian; ", Isril (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The issuance of ministry of home affairs No. 37/2007 on rural budget managementprovides the foundation for autonomous rural village in practice, not just a normative. Releaseof this regulation was followed by the release of ministry of home affairs 66/2007 on ruraldevelopment planning, so that there is continuity between the rules on planning with ruralbudget management. However, ideal conditions as stated in ministry of home affairs 37/2007was not easy as the practice in the field. Therefore, this study wanted to see the village'sbudgeting management in the case study in Perhentian Raja village, Lubuk Sakat Sub-districtof Kampar district.This study used a qualitative approach in obtaining and analyzing the data, to analysisthe data then theory of the role of organizational and policy form the basis for the study of dataanalysis. The withdrawal technique of informant is conducted with a purposive approach, thedata in this study was obtained through interviews and observation techniques and studydocumentation.The results of this study indicate that rural budget management of Lubuk Sakat villagehas composed and run well. Financial management process that begins the process ofplanning, budgeting, administration, financial reporting, financial accountability and financialoversight. All processes were passed by the village government Lubuk Sakat in managingvillage finances sourced from revenue villages, the balance funds, taxes and levies and othersources that are not binding and lawful. Furthermore, the rural budget management of theLubuk Sakat village administratively but not both in the empirical. That's because many of thebarriers in the financial management techniques Sakat Lubuk village. The obstacles that arebarriers to education officials, unbalanced budget allocation, support facilities, lack ofparticipation, lack of supervision and capacity factor village.Keywords; Management, Finance, Government, Rural